APPLICATION OF SEVEN JUMP METHOD WITH APPROACH TO PROBLEM BASED LEARNING On STUDENTS IN PROGRAM STUDI OF MECHANICAL ENGINEERING EDUCATION FKIP PALANGKARAYA UNIVERSITY ACADEMIC YEAR 2014/2015 - Sri Murwantini; Karelius (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
This study was conducted to determine whether the application of Seven Jump Method (SJM) can improve understanding of concept of electrical measuring instruments on the students in Program Studi of Mechanical Engineering Education FKIP Palangkaraya University Academic Year 2014/2015. SJM implementation phases consisting of pre-discussion, discussion, and after the discussion. Data collection was performed by providing pre-test at the time of pre-discussion and post-test at the time of the postdiscussion. The results showed a significant increase in the value of the pre-test to post-test as well as a change after learning in major categories.